2021
DOI: 10.3389/fmicb.2021.653998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Bacterial Communities of an Invasive and Two Native Caribbean Seagrass Species Sheds Light on the Possible Influence of the Microbiome on Invasive Mechanisms

Abstract: Invasive plants, including marine macrophytes, are one of the most important threats to biodiversity by displacing native species and organisms depending on them. Invasion success is dependent on interactions among living organisms, but their study has been mostly limited to negative interactions while positive interactions are mostly underlooked. Recent studies suggested that microorganisms associated with eukaryotic hosts may play a determinant role in the invasion process. Along with the knowledge of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…In contrast, intraspecific variation involves differences between microbiomes that are associated with different host genotypes or across the biogeographical range of the same species. Both types of variation have been previously reported for seagrass [40,41], mangrove [42,43], and saltmarsh [44][45][46][47] microbiomes, with a focus on each habitat separately. By addressing this question, we may be able to establish generalised patterns of both types of microbial change within and among the three habitats.…”
Section: Figurementioning
confidence: 60%
“…In contrast, intraspecific variation involves differences between microbiomes that are associated with different host genotypes or across the biogeographical range of the same species. Both types of variation have been previously reported for seagrass [40,41], mangrove [42,43], and saltmarsh [44][45][46][47] microbiomes, with a focus on each habitat separately. By addressing this question, we may be able to establish generalised patterns of both types of microbial change within and among the three habitats.…”
Section: Figurementioning
confidence: 60%
“…The number of studies comparing the microbiome of native and invasive species in plants is growing rapidly (Coats and Rumpho, 2014; Aires et al, 2021), but only a few studies have focused on comparing the microbiome of native and invasive animals (Chiarello et al, 2022; Santos et al, 2021). In a recent study, Chiarello et al (2022) found that native mussels shared a substantial fraction of their microbiome with the co-occurring invasive species Corbicula fluminea , indicating that invasive mussels may host microbial communities that are obtained locally.…”
Section: Discussionmentioning
confidence: 99%
“…The extracted DNA was assessed by gel electrophoresis, and the qualified DNA was then stored at −20°C until used for amplification. To preclude amplification of plastid sequences, the primers 799F and 1193R were used to amplify the V5-V7 hypervariable regions of the 16S rRNA gene which has been used in the study of plants and algae microbiota (Zhang et al, 2019;Aires et al, 2021). The amplicon libraries were constructed using TruSeq Nano DNA LT Library Prep Kit (Illumina, San Diego, CA, USA), following the manufacturer's recommendations, and index codes were added.…”
Section: Dna Extraction Pcr Amplification and Illumina Sequencingmentioning
confidence: 99%